Analysis of The Impact of Health Expenditures on Health Status in Nigeria - Musa, Nuhu (Journal of Applied And Theoretical Social Sciences, 2022)
Expenditures on healthcare are vital for the enhancement of health conditions through reduction in infant mortality rate. This study is aimed at investigating the relationship between government spending on health sector and health status in Nigeria using annual time series data from 1986 to 2020. The dependent variable of the model is infant mortality rate used as health indicator while the independent variables include; health capital expenditure, recurrent expenditure, GDP per capita, and level of education. The study employed co-integration and error correction model (ECM) for the analysis. Results indicated that health capital expenditure and recurrent expenditure dampen infant mortality in Nigeria during the period under study. Furthermore, GDP per capita and level of education had negative and insignificant relationship with infant mortality rate. Based on these empirical findings, the study recommended that government should give priority attention to the funding and maintenance of health care system for the realization of better and improved health conditions of citizens.